2015
DOI: 10.1146/annurev-physchem-040214-121344
|View full text |Cite
|
Sign up to set email alerts
|

Upconversion of Rare Earth Nanomaterials

Abstract: Rare earth nanomaterials, which feature long-lived intermediate energy levels and intraconfigurational 4f-4f transitions, are promising supporters for photon upconversion. Owing to their unique optical properties, rare earth upconversion nanomaterials have found applications in bioimaging, theranostics, photovoltaic devices, and photochemical reactions. Here, we review recent advances in the photon upconversion processes of these nanomaterials. We start by considering energy transfer models involved in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(67 citation statements)
references
References 122 publications
0
67
0
Order By: Relevance
“…2(d)). The overall emission intensity of NaYF 4 :Er/Tm nanocrystals was remarkably enhanced after NaYF 4 shell coating owing to elimination of quenchers on the surface of NaYF 4 :Er/Tm nanoparticles 10, 17 . Note that the enhancement factor for red emission is more prominent than that of the green emission, further elevating the red to green ratio.…”
Section: Resultsmentioning
confidence: 99%
“…2(d)). The overall emission intensity of NaYF 4 :Er/Tm nanocrystals was remarkably enhanced after NaYF 4 shell coating owing to elimination of quenchers on the surface of NaYF 4 :Er/Tm nanoparticles 10, 17 . Note that the enhancement factor for red emission is more prominent than that of the green emission, further elevating the red to green ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, tremendous attention has been paid on the synthesis and spectroscopic analysis of RE ion‐doped UCNPs with controlled shapes, sizes, and crystalline phases . A variety of synthetic methods have been identified that include coprecipitation, hydrothermal/solvothermal process, seed‐mediated heat‐up approach, decomposition of mixed trifluoroacetates, template method, sol–gel method, and Ostwald‐ripening epitaxial shell growth, which have been reviewed in many papers as well . These methods are the most widely used methods for the synthesis of UCNPs because they offer precise control over phases, sizes, and morphologies of UCNPs.…”
Section: Synthesis Of Ucnpsmentioning
confidence: 99%
“…In recent years, RE compounds have been applied to NIR‐II fluorescence imaging, and exceptional fluorescence tunability though the doping of different RE metal ions has been demonstrated . The fluorescence of RE compounds is attributed to resonant energy transfer between the sensitizer and RE activator dopant . Tuning the atomic makeup will be beneficial for the generation of sharp, narrow emission bands in the NIR‐II region .…”
Section: Re Compoundsmentioning
confidence: 99%
“…[94][95][96] The fluorescenceo fR Ec ompounds is attributed to resonant energy transfer between the sensitizer and RE activator dopant. [97,98] Tuning the atomicm akeup will be beneficial for the generation of sharp, narrow emission bands in the NIR-II region. [94] Similart oo ther inorganic fluorophores, RE compounds exhibit minimal photobleaching under whole-body imaging conditions;t his indicates the possibility of monitoring disparate biological processes through multicolor imaging over extendedp eriodsoft ime.…”
Section: Re Compoundsmentioning
confidence: 99%